A Sufficient Condition for Asymptotic Stability of Discrete-Time Interval System with Delay - Wei Zhu (Discrete Dynamics in Nature and Society)
The asymptotic stability of discrete-time interval system with delay is discussed. A new sufficient condition for preserving the asymptotic stability of the system is presented by means of the inequality techniques. By mathematical analysis, the stability criterion is less conservative than that in previous result. Finally, one example is given to demonstrate the applicability of the present scheme.